Peran Orang Tua terhadap Perkembangan Moral pada Generasi Melenial - Hartanto, Agit Purwo (MEDI KONS: Jurnal Prodi Bimbingan dan Konseling UNISRI Surakarta, 2022)
Moral is a habit based on the rules or norms that apply in society. This study aims to examine the importance of the role of parents in the moral development of the millennial generation. This research method uses library research, namely research whose object of study uses library data in the form of books as a data source by reading, studying and also analyzing various existing literature in the form of articles and books as a collaboration of empirical studies and theoretical studies. The results of this study are that there are several roles of parents that can be sought to contribute to their children as part of the millennial generation.